Changing climate mediates sapsucker (Aves: Sphyrapicus) hybrid zone movement. Issue 22 (12th October 2016) - Billerman, Shawn M.; Murphy, Melanie A.; Carling, Matthew D.
Abstract: Hybrid zones, where two divergent taxa meet and interbreed, offer unique opportunities to investigate how climate contributes to reproductive isolation between closely related taxa and how these taxa may respond to climatic changes. Red‐naped ( Sphyrapicus nuchalis ) and Red‐breasted ( Sphyrapicus ruber ) sapsuckers (Aves: Picidae) hybridize along a narrow contact zone that stretches from northern California to British Columbia. The hybrid zone between these species has been studied extensively for more than 100 years and represents an excellent system for investigations of the evolution of reproductive isolation. Shifts in the proportions of phenotypes at hybrid localities since 1910 that were inferred using specimens from museum collections were confirmed using species distribution models. We predicted the historical, current, and future distributions of parental and hybrid sapsuckers using Random Forests models to quantify how climate change is affecting hybrid zone movement in the Pacific Northwest. We found observed distribution shifts of parental sapsuckers were likely the result of climate change over the past 100 years, with these shifts predicted to continue for both sapsuckers over the next 80 years. We found Red‐breasted Sapsuckers are predicted to continue to expand, while Red‐naped Sapsuckers are predicted to contract substantially under future climate scenarios. As a result of the predicted changes, the amount of overlap in the distribution of these sapsuckers may decrease. Using hybrid phenotypes, we found the climate niche occupied by the hybrid zone is predicted to disappear under future conditions. The disappearance of this climate niche where the two parental species come into contact and hybridize may lead to a substantial reduction in genetic introgression. Understanding the impacts of global climate change on hybrid zones may help us to better understand how speciation has been shaped by climate in the past, as well as how evolution may respond to climate change in the future. Abstract : We found that climate has likely influenced hybrid zone movement between Red‐naped and Red‐breasted Sapsuckers in the Pacific Northwest of the United States over the past 100 years. A combination of warmer winter temperatures and precipitation changes is likely driving this change and is predicted to continue to influence movement of these two species and where they overlap and hybridize. As a result of climate change, the amount of overlap between these two species is also predicted to decrease, possibly resulting in reduced hybridization.